Revisiting U.S – China Aggressive Use of Outer Space: A Comprehensive International Law Outlook Towards Military Activities in Outer Space - Muhammad, Alif Nurfakhri (Indonesian Journal of International Law, 2019)
Outer Space, as the area on which freedom of use is guaranteed by the Treaty, creates a condition in which nations conduct their military activities. These activities however, were only limited to those conducted using nuclear weapons and/or containing nuclear materials. The principle of Peaceful Uses of Outer Space has been proven inadequate to regulate these activities. This has resulted to launches of weapons to Outer Space to destroy satellites, as conducted by the United States and China. These launches, whatever the purposes are, may cause hazardous repercussion to other State’s activity in Outer Space. This article will comprehensively elaborate on related International Law and other measures which regulate military activities in Outer Space, especially on the launch of non-nuclear weaponry under any purposes. From these analyses, we can conclude that however inadequate the Outer Space Treaty article’s stipulation in the matter, there are other stipulations of international law that we can gather that regulates military activity in Outer Space.